1994
DOI: 10.1164/ajrccm.149.6.8004291
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory disorders and atopy in Danish refuse workers.

Abstract: This survey describes respiratory and mucosal symptoms of garbage-handling and recycling workers in Denmark. The study includes 20 paper-sorting workers, eight compost workers, and 44 garbage-handling workers. As a control group, 119 workers from water purification plants of Copenhagen were chosen; workers in our study had a lower mean age and shorter mean employment time than did members of the control group. There was no significant difference in tobacco consumption between the groups. Garbage-handling worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 13 publications
0
63
0
Order By: Relevance
“…Likewise, no clinically significant decrease in FVC, FEV 1 , or FEV 1 /FVC was found. Thus, there is some heterogeneity between the conclusions of studies on this topic (Thorn et al 2002;Yang et al 2001;Bunger et al 2000;Friis et al 1999;Rylander 1999;Thorn et al 1998;Ivens et al 1997;Zuskin et al 1996;Poulsen et al 1995;Sigsgaard et al 1994;Zuskin et al 1993;Malmros et al 1992;Nethercott and Holness 1988;Rylander et al 1977;Rufener-Press et al 1976). Both true differences in exposure and methodological factors explain these apparently contradictory findings.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, no clinically significant decrease in FVC, FEV 1 , or FEV 1 /FVC was found. Thus, there is some heterogeneity between the conclusions of studies on this topic (Thorn et al 2002;Yang et al 2001;Bunger et al 2000;Friis et al 1999;Rylander 1999;Thorn et al 1998;Ivens et al 1997;Zuskin et al 1996;Poulsen et al 1995;Sigsgaard et al 1994;Zuskin et al 1993;Malmros et al 1992;Nethercott and Holness 1988;Rylander et al 1977;Rufener-Press et al 1976). Both true differences in exposure and methodological factors explain these apparently contradictory findings.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen occupational studies measured personal exposure of compost workers to different bioaerosol components (Bünger et al, 2007;Crook et al, 2008;Drew et al, 2007;Douwes et al, 1997;Epstein et al, 2001;Krajewski et al, 2002;Schlosser et al, 2009;Sigsgaard et al, 1994;Stagg et al, 2010;Sykes et al, 2011;Taha et al, 2007;Wheeler et al, 2001), detecting significantly high concentrations of actinomycetes, Aspergillus fumigatus, fungi, and endotoxin (Stagg et al, 2010), and elevated personal exposure levels of endotoxin in workers, particularly during composting agitation activities (Sykes et al, 2011). Four occupational studies measured mesophilic mould/fungi (Reinthaler et al, 2004;Schlosser et al, 2009;Tolvanen et al, 2005;van Kampen et al, 2014).…”
Section: Exposure Studiesmentioning
confidence: 99%
“…Nonsignificant health results are presented in Appendix 9. * The study information from Sigsgaard, Hansen, and Malmros (1997) is from a conference paper, as the results were not reported in Sigsgaard et al (1994). (1.0-2.1), unusual tiredness =1.5 (1.1-2.0), fever/shivering = 1.7 (1.1-2.5), joint pain = 1.5 (1.1-2.1), muscular pain =1.5 (1.1-2.0)…”
Section: Bias Assessmentmentioning
confidence: 99%
“…The health risks associated with this type of industry are, however, not yet clear. The few studies that assessed health risks [1][2][3][4][5][6] showed that workers in waste handling, particularly workers collecting and processing domestic organic waste for composting, are at risk of developing various health effects-such as respiratory symptoms, systemic influenza-like symptoms, and gastrointestinal problems.…”
mentioning
confidence: 99%